Cerdas Mengelola Keuangan Rumah Tangga Bagi Ibu-Ibu Kelurahan Mojolangu Kota Malang - Bunyamin Bunyamin; Siti Munfaqiroh; Lailatus Sa’adah; Rina Rahmawati; Widanarni Pudjiastuti; Lindananty , Lindananty; Dwi Danesti Deccasari; Marli Marli; Didik Priyo Sugiharto; Zainul Arifin; Yupono Bagyo; Wiyarni Wiyarni; Eko Sudjawoto (Jurnal ABM Mengabdi, 2022)
Family financial planning is a strategy to achieve family financial goals in the short and long term. Good financial planning certainly cannot be separated from good financial management, because good financial management attitudes start from the implementation of good financial attitudes. Partners in this Community Service Program are women in the Mojolangu village, Lowokwaru sub-district, Malang city. The method of implementing this service is the interview, presentation and discussion method. Based on the results of the interviews, it can be concluded that the problems that occurred, namely: (1) lack of public knowledge in managing family finances and also good financial planning. (2) The community has not recorded their results (3) there are still many mothers who lack knowledge about the importance of saving as a priority. The solutions offered in this service are as follows: (1) provide education/knowledge about the importance of how to manage family finances smartly and carefully, (2) the service team provides education/knowledge about the importance of recording and household financial income from business results, (3) the proposing team will provide education / insight related to the importance of knowledge about saving and investment activities.